(Un)Conventional monetary policy : how do negative policy rates affect banks? - Barreiras, Joana Maria Raposo (2021)
In June 2014, the ECB’s decision to cut its deposit facility rate (DFR) to -10 b.p. broke with the idea of an unsurpassable zero lower bound. At this level, people would convert deposits into cash to escape nominal devaluation. This new unconventional monetary policy’s impact on bank profitability is being extensively studied, without no full consensus being reached yet. We assess the Negative Interest Rate Policy (NIRP) effects on bank profitability, using a panel dataset of 143 Euro Area listed banks over the period from 2005 to 2019. This study employed a panel data linear regression analysis using relevant income components (Net Interest Income (NII), Net Non-interest Income (NNI), and Loan Losses Provisions (LLP) as a ratio to Total Assets) and the overall profitability (ROA) as measures of bank profitability. The results show a benign impact of NIRP on ROA, suggesting a lowering of LLP and an increase in NNI weighting a deteriorating effect on NII. Additionally, we show some evidence in favor of high-deposit banks being more vulnerable to the NIRP since they are reluctant to pass on these rates to retail depositors.